Fabric-based composite photocatalytic material as well as preparation method and application thereof

By loading titanium carbide and bismuth vanadate onto cotton fabrics, a fabric-based composite photocatalytic material was prepared, which solved the secondary pollution problem of existing photocatalytic materials when treating wastewater in the textile printing and dyeing industry, and achieved efficient photocatalytic degradation effect and good cycle stability.

CN119588418APending Publication Date: 2025-03-11WUHAN TEXTILE UNIV +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411582914.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Due to the poor photocatalytic materials such as bismuth vanadate, due to their poor photogenerating charge transmission capabilities, they have secondary pollution problems when dealing with wastewater in the textile printing and dyeing industry, which limits their application.

Method used

By loading titanium carbide and bismuth vanadate onto cotton fabrics, using aqueous polyurethane as crosslinking agents, a fabric-based composite photocatalytic material was prepared. The material is prepared by ultrasonic and water bath oscillation. The mass ratio of bismuth vanadate to titanium carbide is 0.3 to 3, the mass concentration of bismuth vanadate is 1 to 4.5 g/L, and the concentration of aqueous polyurethane is 0.5 to 5 g/L.

Benefits of technology

This fabric-based composite photocatalytic material showed a removal rate of 96.0% when photocatalyzed methylene blue, and had good cycling stability, proving its excellent photocatalytic properties and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588418A_ABST
    Figure CN119588418A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalytic materials, in particular to a fabric-based composite photocatalytic material as well as a preparation method and application thereof. The preparation method of the fabric-based composite photocatalytic material comprises the following steps: titanium carbide is added into deionized water for ultrasonic treatment, then bismuth vanadate is added for mixed ultrasonic treatment, waterborne polyurethane and cut cotton fabric are added after ultrasonic treatment is completed, a sample is taken out after water bath oscillation is performed for a period of time, the sample is washed, and vacuum drying is performed to obtain the fabric-based composite photocatalytic material. The fabric-based bismuth vanadate / titanium carbide composite material is prepared by taking waterborne polyurethane as a cross-linking agent and loading two catalysts, namely titanium carbide and bismuth vanadate, onto a cotton fabric through a one-bath method, and has excellent photocatalytic performance and recoverability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalytic materials, and in particular to a fabric-based composite photocatalytic material and a preparation method and application thereof. Background Art

[0002] Wastewater from the textile printing and dyeing industry contains a large amount of pollutants such as organic matter, suspended solids and dyes. They are characterized by high chroma, high toxicity and high biochemical oxygen demand, so how to treat wastewater has become a major problem. Currently, common wastewater treatment methods include physical methods, biochemical methods, ozone oxidation, Fenton reagent oxidation, physical and chemical methods, wet (catalytic) oxidation and photocatalytic oxidation. Among them, photocatalytic oxidation refers to the generation of photogenerated electrons and holes by photocatalysts after being irradiated by light sources. They have strong reducing and oxidizing properties, respectively, and can react with H2O and O2 molecules to produce highly oxidizing ·OH and ·O2 - , thereby oxidizing organic pollutants in water into H2O and CO2. Compared with other methods, photocatalytic oxidation is simple, widely applicable, more efficient, and environmentally friendly. Bismuth vanadate has attracted much attention among photocatalytic materials due to its low band gap, non-toxicity, and simple preparation. However, its use is limited by its poor photogenerated charge transport ability, the easy recombination of electron-hole pairs, and the resulting secondary water pollution. Summary of the Invention

[0003] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and to provide a fabric-based composite photocatalytic material and a preparation method and application thereof.

[0004] The present invention discloses a method for preparing a fabric-based composite photocatalytic material, wherein titanium carbide is added to deionized water and sonicated, then bismuth vanadate is added and sonicated again. After sonication, aqueous polyurethane and cut cotton fabric are added, and the sample is taken out and washed after being shaken in a water bath for a period of time and then vacuum dried to obtain the fabric-based composite photocatalytic material.

[0005] Furthermore, the mass ratio of bismuth vanadate to titanium carbide is 0.3-3.

[0006] Furthermore, the mass concentration of bismuth vanadate is 1 to 4.5 g / L.

[0007] Furthermore, the concentration of the waterborne polyurethane is 0.5 to 5 g / L.

[0008] Furthermore, the preparation method of bismuth vanadate is as follows: bismuth nitrate pentahydrate is dissolved in nitric acid solution and completely dissolved by magnetic stirring. Then ammonium metavanadate is added, and ammonia water is slowly added dropwise to adjust the pH. After stirring, it is placed in a reaction vessel for high-temperature treatment, and then cooled, washed, and dried.

[0009] Furthermore, the concentration of the nitric acid solution is 2 mol / L; the molar mass ratio of bismuth nitrate pentahydrate to ammonium metavanadate is 0.5–2, the molar mass concentration of the bismuth nitrate solution is 0.01–0.10 mol / L, the pH is adjusted to 5–7; the temperature of the reactor is 130℃, and the temperature of vacuum drying is 70–100℃.

[0010] Further, the preparation method of titanium carbide is as follows: Lithium fluoride is dissolved in concentrated hydrochloric acid. After it is completely dissolved, aluminum carbide is added in small amounts several times. The lid is closed with a gap left. After magnetic stirring, it is first washed with hydrochloric acid, then washed with deionized water until the pH is greater than 6, and finally freeze-dried.

[0011] Furthermore, the mass ratio of lithium fluoride to aluminum carbide is 1:1, the concentration of concentrated hydrochloric acid is 9–12 mol / L, the freeze-drying time is 12–24 h, the reaction temperature is 45 °C, and the concentration of hydrochloric acid used for washing is 0.5–2 mol / L.

[0012] A fabric-based composite photocatalytic material prepared by the method described above.

[0013] An application of the fabric-based composite photocatalytic material as described above, used as a photocatalyst for the degradation of methylene blue.

[0014] This invention uses waterborne polyurethane as a crosslinking agent and loads two catalysts, titanium carbide and bismuth vanadate, onto cotton fabrics via a one-bath method to prepare a fabric-based bismuth vanadate / titanium carbide composite material, which exhibits excellent photocatalytic performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a micro-electron microscopy image of the fabric-based composite photocatalytic material prepared in Example 1;

[0016] Figure 2 The image shows the UV-Vis spectrum of the fabric-based composite photocatalytic material prepared in Example 1 degrading methylene blue.

[0017] Figure 3 The image shows the degradation effect of the fabric-based composite photocatalytic material prepared in Example 1 on methylene blue.

[0018] Figure 4 This is a diagram illustrating the cyclic degradation effect of the fabric-based composite photocatalytic material prepared in Example 1 on the degradation of methylene blue.

[0019] Figure 5 The degradation effect of the fabric-based composite photocatalyst material, BiVO4, and MXene on methylene blue prepared in Example 1 is shown in the figure.

[0020] Figure 6 The images show the degradation effect of the fabric-based composite photocatalytic materials prepared in Examples 1-4 on methylene blue.

[0021] Figure 7 Photoluminescence spectra of BiVO4, MXene, and the fabric-based composite photocatalyst material prepared in Example 1. DETAILED DESCRIPTION

[0022] The following are specific embodiments of the present invention, which are described in conjunction with the accompanying drawings. However, the present invention is not limited to these embodiments.

[0023] Preparation of bismuth vanadate

[0024] 1.4522 g of bismuth nitrate pentahydrate was dissolved in a 2 mol / L nitric acid solution and completely dissolved by magnetic stirring. Then, 0.3509 g of ammonium metavanadate was added and ammonia was slowly added dropwise to adjust the pH to 5. After stirring for 30 min, the mixture was placed in a reactor and reacted at 130°C for 24 h. After cooling, the mixture was filtered and washed with deionized water and ethanol, and finally dried in a vacuum oven at 80°C for 4 h.

[0025] Preparation of titanium carbide

[0026] Dissolve 1g of lithium fluoride in 9mol / L concentrated hydrochloric acid. After it is completely dissolved, add 1g of aluminum titanium carbide in small amounts several times. Cover with a lid leaving a gap. Heat in a water bath at 45°C and stir for 24 hours. Then wash with 1mol / L hydrochloric acid three times, then with deionized water until the pH is greater than 6, and finally freeze-dry for 12 hours.

[0027] Example 1:

[0028] First, take 0.05g of titanium carbide and add it to 50mL of deionized water and ultrasonicate for 15 minutes, then add 0.15g of bismuth vanadate and mix with ultrasonication for 15 minutes. After the ultrasonication is completed, add 5mg of aqueous polyurethane and cut 4×4cm cotton fabric, put it into a water bath and oscillate at room temperature for 24 hours. Then take out the sample, wash it with deionized water, and vacuum dry it at 80℃ for 4 hours to obtain a fabric-based composite photocatalytic material.

[0029] Example 2:

[0030] First, take 0.1g of titanium carbide and add it to 50mL of deionized water and ultrasonicate for 15 minutes, then add 0.1g of bismuth vanadate and mix with ultrasonication for 15 minutes. After the ultrasonication is completed, add 5mg of aqueous polyurethane and cut 4×4cm cotton fabric, put it into a water bath and oscillate for 24 hours. Then take out the sample, wash it with deionized water, and vacuum dry it at 80℃ for 4 hours to obtain a fabric-based composite photocatalytic material.

[0031] Example 3:

[0032] First, take 0.15g of titanium carbide and add it to 50mL of deionized water and ultrasonicate for 15 minutes. Then add 0.05g of bismuth vanadate and mix with ultrasonication for 15 minutes. After the ultrasonication is completed, add 5mg of aqueous polyurethane and cut 4×4cm cotton fabric. Place it in a water bath and oscillate at room temperature for 24 hours. Then take out the sample, wash it with deionized water, and vacuum dry it at 80℃ for 4 hours to obtain a fabric-based composite photocatalytic material.

[0033] Example 4:

[0034] (3) First, 0.05 g of titanium carbide was added to 50 mL of deionized water and ultrasonicated for 15 minutes. Then, 0.15 g of bismuth vanadate was added and ultrasonicated for 15 minutes. After the ultrasonication, 50 mg of aqueous polyurethane and 4 × 4 cm cut cotton fabric were added. The fabric was placed in a water bath and oscillated at room temperature for 24 hours. The sample was then taken out, washed with deionized water, and vacuum dried at 80 ° C for 4 hours to obtain a fabric-based composite photocatalytic material.

[0035] Figure 1 This is a microscopic electron microscope image of the fabric-based composite photocatalytic material prepared in Example 1. Figure 1 (a) It can be clearly seen that a large amount of bismuth vanadate and titanium carbide are loaded on the cotton fabric. Figure 1 (b) It can be seen that bismuth vanadate is not only loaded on the fabric, but also partially loaded on the surface of titanium carbide, which is more conducive to the synergistic degradation of methylene blue by the two. Figure 1 (c) It can be observed that the surface of the cotton fabric is very smooth, indicating that the water-based polyurethane forms a film on the surface of the cotton fabric, thereby adhering bismuth vanadate and titanium carbide to the fabric surface. It can also be seen that bismuth vanadate has a nanoscale structure and titanium carbide has a multilayer structure, and the thickness of the single layer is also nanoscale.

[0036] Degradation test of methylene blue

[0037] The relative residual concentration (C / C0) of the methylene blue solution at different times was tested, and its degradation rate ΔC / C0 was calculated.

[0038] The formula for calculating C / C0 is: C / C0 = A / A0. Where C is the concentration of the residual methylene blue solution, C0 is the concentration of the original methylene blue solution, A is the absorbance of the residual methylene blue solution, and A0 is the absorbance of the original methylene blue solution. The formula for calculating the degradation rate is: ΔC / C0 = (A0 - A) / A0.

[0039] The maximum absorption wavelength of methylene blue is 664nm, corresponding to Figure 2 The peak of each curve, therefore, the change in the peak value of the curve can show the degree of degradation of methylene blue, and the degradation effect of methylene blue at different times can be calculated through the absorbance at 664nm.

[0040] The fabric-based composite photocatalytic material prepared in Example 1 was used as a catalyst to oxidize and decompose methylene blue. The results are as follows: Figure 3 As shown, Figure 3 The entire system was shielded from light for the first 30 minutes to achieve saturated adsorption. For the next 160 minutes, condensed water was passed through the system using a xenon lamp to simulate sunlight, stimulating the catalyst to oxidize and decompose methylene blue. After 190 minutes of adsorption and degradation, the removal rate of methylene blue in the water reached 96.0%, demonstrating the strong photocatalytic performance of the prepared composite material.

[0041] Figure 4 The degradation of methylene blue by the fabric-based composite photocatalytic material prepared in Example 1 was recorded three times. The material was rinsed and dried after each use. The degradation rate reached 96.0% on the first, 92.5% on the second, and 85.4% on the third, demonstrating the excellent cyclic stability of the prepared photocatalytic composite material.

[0042] Figure 5 The degradation effects of the fabric-based composite photocatalytic material prepared in Example 1, bismuth vanadate alone, and titanium carbide alone on methylene blue were recorded. Figure 5 It can be seen that due to the large specific surface area given by the multilayer structure of MXene, the adsorption of methylene blue is very significant, but the photocatalytic degradation effect is very poor, indicating that MXene is not capable of recycling; while BiVO4 has a narrower band gap width and a wider photoexcitation range, which makes it easier to be photoexcited to produce photogenerated electron pairs and holes, so its photocatalytic degradation effect is relatively strong, but its adsorption capacity is relatively poor, resulting in a decrease in its degradation rate when the concentration of the dye decreases, and due to its small particle size, it is more likely to adhere to the container, making it difficult to recycle. After combining these two with cotton fabric to prepare a composite material, MXene improves the adsorption performance of the material, and can slow down the recombination of photogenerated carriers, thereby improving the photocatalytic performance of the material, and is easier to recycle, making the material recyclable.

[0043] Figure 6 The degradation effects of the fabric-based composite photocatalytic materials prepared in Examples 1-4 on methylene blue were recorded. Figure 6 It can be seen that Example 1 has the best degradation effect on methylene blue, indicating that the synergistic effect of bismuth vanadate and titanium carbide is optimal at this time. As the proportion of titanium carbide increases, the adsorption performance of the material is slightly improved, but the degradation effect is significantly worsened. In Example 4, due to the excessive amount of water-based polyurethane forming a thin film on the surface of the catalyst, direct contact between the material and methylene blue is prevented, thereby reducing the degradation efficiency.

[0044] Figure 7Photoluminescence spectra of BiVO4, MXene and fabric-based composite photocatalytic materials prepared in Example 1. Figure 7 It can be seen that the fluorescence signal intensity of the composite material is much lower than that of the two single catalysts, which indicates that the recombination of free electrons and holes generated by light excitation is slower, which prolongs the life of carriers and enhances the photocatalytic activity. Figure 5 This shows that the composite of MXene and BiVO4 can accelerate the mobility of photogenerated electron-hole pairs, thereby significantly improving the photocatalytic efficiency.

[0045] Any matters not mentioned above shall be subject to the existing technology.

[0046] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art of the present invention may make various modifications or additions to the described specific embodiments or replace them in similar ways, but they will not deviate from the direction of the present invention or exceed the scope defined by the appended claims. Those skilled in the art should understand that any modifications, equivalent replacements, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a fabric-based composite photocatalytic material, characterized in that: Titanium carbide is added to deionized water for ultrasonic treatment, and then bismuth vanadate is added for mixed ultrasonic treatment. After the ultrasonic treatment, waterborne polyurethane and cut cotton fabric are added. After oscillating in a water bath for a period of time, the sample is taken out, washed, and vacuum dried to obtain the fabric-based composite photocatalytic material.

2. The preparation method according to claim 1, characterized in that: The mass ratio of bismuth vanadate to titanium carbide is 0.3-3.

3. The preparation method according to claim 1, characterized in that: The mass concentration of bismuth vanadate is 1-4.5 g / L.

4. The preparation method according to claim 1, characterized in that: The concentration of waterborne polyurethane is 0.5-5 g / L.

5. The preparation method according to claim 1, characterized in that: The preparation method of bismuth vanadate is as follows: dissolving bismuth nitrate pentahydrate in nitric acid solution, completely dissolving it by magnetic stirring, then adding ammonium metavanadate, slowly adding ammonia water to adjust the pH, stirring, placing it in a reactor for high-temperature treatment, waiting for it to cool down, washing and drying.

6. The preparation method according to claim 5, characterized in that: The concentration of the nitric acid solution is 2 mol / L; the molar mass ratio of bismuth nitrate pentahydrate to ammonium metavanadate is 0.5-2, the molar mass concentration of the bismuth nitrate solution is 0.01-0.10 mol / L, and the pH is adjusted to 5-7; the temperature of the reaction kettle is 130° C., and the temperature of the vacuum drying is 70-100° C.

7. The preparation method according to claim 1, characterized in that: Preparation method of titanium carbide: dissolve lithium fluoride in concentrated hydrochloric acid, add aluminum carbide in small amounts and multiple times after it is completely dissolved, cover with a lid and leave a gap, wash with hydrochloric acid after magnetic stirring, then wash with deionized water until the pH is greater than 6, and finally freeze-dry.

8. The preparation method according to claim 7, characterized in that: The mass ratio of lithium fluoride to aluminum titanium carbide is 1:1, the concentration of concentrated hydrochloric acid is 9-12 mol / L, the freeze-drying time is 12-24 hours; the reaction temperature is 45°C, and the concentration of hydrochloric acid used for washing is 0.5-2 mol / L.

9. A fabric-based composite photocatalytic material prepared by the preparation method according to any one of claims 1 to 8.

10. An application of the fabric-based composite photocatalytic material as claimed in claim 9, characterized in that: Used as a photocatalyst to degrade methylene blue.

Citation Information

Patent Citations

  • Fabric for treating printing and dyeing wastewater and preparation method thereof

    CN106334585A

  • Preparation method of finishing agent for shoe upper fabric

    CN108625171A

  • Method for increasing binding strength of copper-cobalt-nickel ferrite compound on cotton fabric

    CN110359294A

  • Nanosheet-assembled porous rod-like BiVO4 triangular prism material and preparation method thereof

    CN116143170A

  • Laminated composite photocatalyst with mesoporous membrane as well as preparation method and application of laminated composite photocatalyst

    CN116273102A